2017
DOI: 10.1007/s00432-017-2381-y
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1, PRPF40A, and UCP2 correlate with hypoxia markers in non-small cell lung cancer

Abstract: PurposeCollagen 1A1 (COL1A1), RNA-binding and pre-mRNA Processing Factor (PRPF40A), and Uncoupling Protein 2 (UCP2) were identified as downstream effectors of cytoglobin (CYGB), which was shown implicated in tumour biology. Although these three genes have been previously associated with cancer, little is known about their status in lung malignancies.MethodsHereby, we investigated the expression and promoter methylation of COL1A1, PRPF40A, and UCP2 in 156 non-small cell lung cancer (NSCLC) and adjacent normal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 31 publications
3
44
0
1
Order By: Relevance
“…UCP3 was also linked to the overexpression of glucose and monocarboxylate transporters. This is in accordance with a previous study where UCP2 expression was related to hypoxia markers in NSCLC 21 . This direct association of UCPs with anaerobic glycolysis may explain the inverse association found between UCP3 expression and necrosis, since intensification of glycolytic pathways, under poor blood flow and oxygen availability conditions, certainly offers a survival advantage to cancer cells.…”
Section: Discussionsupporting
confidence: 94%
“…UCP3 was also linked to the overexpression of glucose and monocarboxylate transporters. This is in accordance with a previous study where UCP2 expression was related to hypoxia markers in NSCLC 21 . This direct association of UCPs with anaerobic glycolysis may explain the inverse association found between UCP3 expression and necrosis, since intensification of glycolytic pathways, under poor blood flow and oxygen availability conditions, certainly offers a survival advantage to cancer cells.…”
Section: Discussionsupporting
confidence: 94%
“…In the EC ceRNA network, sponging of overexpressed lncRNA AC009093.1 and under expressed lncRNA MAGI2-AS3, relieved their targets COL1A1 and COL5A2 from being suppressed by hsa-mir-143. Previous studies have suggested that hsa-mir-143 functions as a tumor suppressor in several cancer types [36,37], and COL1A1 has been shown to act as an oncogene to regulate tumors [38][39][40]. Our ndings implied that hsa-mir-143 may function as a tumor suppressor by targeting COL1A1 and COL5A2 in EC and competing with lncRNA MAGI2-AS3/AC009093.1.…”
Section: Discussionsupporting
confidence: 49%
“…Our previous results supported that the downregulation of miR-29a in IPF is associated with the overexpression of COL1A1 gene in BAL cells, confirming the active role of the miR-29a/COL1A1 pathway in AMs and lung tissue, while the expression profile of COL1A1 in LC has not been yet clarified. COL1A1 may be involved in carcinogenesis as aberrant expression levels were revealed in several malignancies including hepatocellular carcinoma ( 42 ), NSCLC tissue ( 43 ) and in malignant gastric tissue ( 44 ). Our findings, however, showed significantly increased levels of COL1A1 in IPF relative to LC in BAL cells that establishes the characteristic fibrotic profile of BAL cells in IPF, which appears to be lacking in LC BAL cells.…”
Section: Discussionmentioning
confidence: 99%